Introductory statistical genetics for plant breeding 2 - van Eeuwijk, Fred (Henry Stewart Talks, 2016)
G→P models II, QTL mapping as an example of a G→P model, Example of GxE analysis: Finlay Wilkinson regression, Example of MET QTL mapping